Matsuda–Heck reaction with arenediazonium tosylates in water - Kutonova, Ksenia V.; Trusova, Marina E.; Stankevich, Andrey V.; Postnikov, Pavel S.; Filimonov, Victor D. (Beilstein Journal of Organic Chemistry, 2015)
An environmentally friendly Matsuda–Heck reaction with arenediazonium tosylates has been developed for the first time. A range of alkenes was arylated in good to quantitative yields in water. The reaction is significantly accelerated when carried out under microwave heating. The arylation of haloalkylacrylates with diazonium salts has been implemented for the first time.
Keywords: alkyl cinnamates; diazonium salts; Matsuda–Heck reaction; microwave-assisted synthesis; stilbenes